SAT-254 Desmopressin Stimulation Test in a Pregnant Patient with Cushing’s Syndrome - Warachit, Wasita (J Endocr Soc, 2020)
Background: Cushing’s syndrome (CS) in pregnancy is a rare condition. Accurate diagnosis and appropriate treatment are necessary due to increased morbidity and mortality in the fetus and mother with active CS. However, hormonal changes during pregnancy and limitations in terms of teratogenicity complicates the diagnosis of CS. Clinical case: A 27-year-old female presented at gestational age (GA) of 8 weeks with a 2-month history of proximal muscle weakness. She had 20-kg weight gain in 2 years before hypertension, prediabetes and pulmonary tuberculosis developed at the age of 25. On physical examination, her blood pressure was 160/100 mmHg. She had moon face, buffalo hump, wide purplish striae and hirsutism without signs of virilization. At GA 9 weeks, her morning cortisol was 32 μ;g/dL (883 nmol/L). Her salivary cortisol was 0.7 μ;g/dL (19 nmol/L) and a mean 24-hour urinary free cortisol was 237 μ;g/d (654 nmol/d), which were above reference ranges. Adrenocorticotropic hormone (ACTH) were 48 pg/mL (11 pmol/L) and 40 pg/mL (9 pmol/L). Dehydroepiandrosterone sulphate was 378 μ;g/dL (10 nmol/L). A non-gadolinium enhanced magnetic resonance imaging (MRI) at GA 12 weeks did not reveal a pituitary mass. Desmopressin stimulation test was carried out at GA 14 weeks. Her baseline cortisol was 31 μ;g/dL (855 nmol/L) and ACTH was 35 pg/mL (8 pmol/L). Her ACTH increased 70% at 15 minutes after desmopressin stimulation, with an absolute difference between basal and peak ACTH of 24 pg/mL (5 pmol/L). MRI pituitary gland with gadolinium at GA 14 weeks revealed an 8-mm adenoma at right inferolateral aspect of pituitary gland. Transsphenoidal surgery with selective adenomectomy was done at GA 18 weeks without immediate complications. Pathological findings showed a segment of pituitary adenoma with ACTH positive cells. After surgery, her morning cortisol was 6 μ;g/dL (166 nmol/L). Hydrocortisone supplement was given and had been continued throughout pregnancy. She successfully gave birth to a term 2300-gram male infant. One year after delivery, she had spontaneous pregnancy and also delivered a term 3300-gram male infant. Cushing’s syndrome had been in remission for 2 years of follow-up. Conclusion: Hormonal changes during pregnancy lead to an increased in ACTH after 7 weeks of gestation. Desmopressin test can be a safe and reliable test to differentiate between ACTH-dependent and ACTH-independent CS. Because a non-gadolinium enhanced MRI may not always detect pituitary microadenoma, this raises the necessity of the use of MRI with gadolinium as an initial imaging in pregnant patients with ACTH-dependent CS. References: Brue T, Amodru V, Castinetti F. Management of Cushing’s syndrome during pregnancy: solved and unsolved questions. Eur J Endocrinol. 2018;178(6):R259-266.